KEKERASAN DALAM RUMAH TANGGA DI BIMA DALAM BINGKAI BUDAYA PATRIARKI - Zuhrah Zuhrah (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
The important in this research is to solve the main factor of violent in household. The research will focus on the perspective of patriarchy culture in Bima. The style of research is field research, researcher be on the field directly, he interview the objects or stakeholders who ever known about the case of violent in household. The sample is taken by using purposive sampling method, and the technique of collect data are using observation, interview, documentation and study literature. Based on the result of research, the case of violent in household in Bima District are more than in Bima City. While the data at Bima City during 2014-2015 only 17% than data at Bima District. The case of violent in household which written at Religious Court are more effected by noting care about household. There are husbands who has not the permanent job, while their wife does not want to help her husband to get job, so they get more income. The violent in household at Bima sometime it be happen to wife or children. The important in this research is to solve the main factor of violent in household. The research will focus on the perspective of patriarchy culture in Bima. The style of research is field research, researcher be on the field directly, he interview the objects or stakeholders who ever known about the case of violent in household. The sample is taken by using purposive sampling method, and the technique of collect data are using observation, interview, documentation and study literature. Based on the result of research, the case of violent in household in Bima District are more than in Bima City. While the data at Bima City during 2014-2015 only 17% than data at Bima District. The case of violent in household which written at Religious Court are more effected by noting care about household. There are husbands who has not the permanent job, while their wife does not want to help her husband to get job, so they get more income. The violent in household at Bima sometime it be happen to wife or children.